2017
DOI: 10.1016/j.jtcvs.2016.12.047
|View full text |Cite
|
Sign up to set email alerts
|

A single center's experience with pacemaker implantation after the Cox maze procedure for atrial fibrillation

Abstract: This study demonstrated lower incidence of PMI after CM procedures than recently reported. When indicated, PMI was not associated with increased short- or long-term morbidity or inferior freedom from atrial arrhythmia. Efforts to increase surgeon training with the CM procedure and postoperative management awareness are warranted to improve rhythm outcome and minimize adverse events and PMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
(50 reference statements)
1
16
0
1
Order By: Relevance
“…Every lesion of the two procedures were exactly the same so, clearly, the elimination of the extensive extracardiac dissection also contributed to the decreased requirements for postoperative pacemakers. This observation has now been confirmed at a single center in more than 700 patients undergoing the cryosurgical maze-III procedure in which only 7% of patients required new pacemakers postoperatively [40].…”
Section: Unmasking Preoperative Sick Sinus Syndromementioning
confidence: 74%
“…Every lesion of the two procedures were exactly the same so, clearly, the elimination of the extensive extracardiac dissection also contributed to the decreased requirements for postoperative pacemakers. This observation has now been confirmed at a single center in more than 700 patients undergoing the cryosurgical maze-III procedure in which only 7% of patients required new pacemakers postoperatively [40].…”
Section: Unmasking Preoperative Sick Sinus Syndromementioning
confidence: 74%
“…According to the literature, the incidence of PPM insertion after the maze procedure is 7%–11% [ 2 , 5 ]. In this study, the incidence of PPM insertion was 5.7% in group A and 2.0% in group B; these rates are consistent with those reported in previous studies [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Performing a maze procedure for the treatment of AF concomitantly with other cardiac procedures can prolong the operation time, cardiopulmonary bypass (CPB) time, and cardiac arrest time. In addition, surgical ablation increases the risk of postoperative bleeding and the need for permanent pacemaker (PPM) insertion [ 2 , 3 ]. However, the substantial benefits from regaining sinus rhythm and atrial contractility warrant the potential risks [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…86 Furthermore, Ad et al have demonstrated that the most common subgroup of patients undergoing the Cox-maze IV to require PPM implantation are those undergoing 2 or more concomitant valve procedures; however, implantation rates remained low at 14% in their series and were not associated with increased morbidity, rhythm failure, or reduction in long-term survival. 87 Exclusion of the right atrial lesion set has been explored to further reduce the PPM implantation rates. Statistically significant reductions in PPM implantation rates were demonstrated in these circumstances with PPM rates as low as 5.4% in the left atrial lesion set only group.…”
Section: Heart Block and Pacemaker Implantationmentioning
confidence: 99%